International Monetary Fund Annual Report 1949. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1949)
This paper reviews key findings of the IMF's Annual Report for the fiscal year ended April 1949. The report highlights that the unbalanced conditions that have characterized the world economic situation since the end of the war still prevail. In many countries, there remains a striking discrepancy between demand and productive capacity, and an even greater discrepancy between the need for imports and capacity to pay for them. Until effective measures are taken to meet these closely related problems, there can be little hope of achieving the expansion of world trade on a multilateral basis.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet